Freedom Memorial Museum Gallery - Gines, Leonido Jr. M. (Sanyata; Vol 1 (2024): Sanyata: Journal of Creative Works of the Philippine Built Environment, 2025)
The Freedom Memorial Museum Gallery displays the human rights abuses during the Martial Law in the 1970s and their stories of how they fought for democracy.